Effect of type of disease-modifying antirheumatic drugs on depression and anxiety of patients with rheumatoid arthritis in Saudi Arabia: a cross-sectional study - Baghdadi, Leena R.; Alhassan, Mohammed K.; Alotaibi, Fawaz H.; Alsuwaida, Anas A.; Shehadah, Ali E.; Alzahrani, Mohammed T. (Frontiers in Psychiatry, 2023)
Background Rheumatoid arthritis (RA) can cause depression and anxiety. This study evaluated the factors associated with depression and anxiety in patients with RA and examined the effect of conventional and biologic disease-modifying antirheumatic drugs (DMARDs). Methods This cross-sectional study was conducted in a regional hospital in Riyadh between March and November 2022 and included 213 patients with RA. Depression and anxiety were measured using the Hospital Anxiety and Depression Scale (HADS) and data about patients’ DMARDs use was obtained from the hospital’s medical records. Results Based on the HADS scores, 35 (16.4%) and 49 (23%) patients with RA had depression and anxiety, respectively. There was a significant association between the level of depression and anxiety and the use of leflunomide and tocilizumab among patients with RA (p = 0.006 and p = 0.009, respectively). Patients with RA who took leflunomide had significantly higher scores for anxiety (β = 0.158, value of p = 0.037) when compared to patients who did not take leflunomide. Patients with RA who took etanercept showed a significantly lower depression score even after adjusting for confounders, including sociodemographic, clinical, and lifestyle factors (β = −0.189, p = 0.043). Conclusion The present study highlighted the prevalence of psychiatric disorders among patients with RA and the level of depression and anxiety may differ between patients with RA depending on the type of DMARDs used. We recommend patients with RA be screened regularly for depression and anxiety to avoid further extra-articular systemic complications associated with RA.